2017
DOI: 10.1177/0003489417713505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluticasone Furoate Nasal Spray on Parameters of Eosinophilic Inflammation in Patients With Nasal Polyposis and Perennial Allergic Rhinitis

Abstract: The levels of RANTES and eotaxin-2 in nasal fluid could be reliable markers for assessing corticosteroid administration outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…2a). Eotaxin and RANTES are chemokines-regulating EOS [32,33]. ELISA results showed that OVA induction increased the contents of eotaxin and RANTES in mouse NALF, while miR-181a-5p overexpression treatment reversed these trends (p < 0.01; Fig.…”
Section: Mir-181a-5p Overexpression Protected Against Treg/ Th17 Immu...mentioning
confidence: 82%
See 1 more Smart Citation
“…2a). Eotaxin and RANTES are chemokines-regulating EOS [32,33]. ELISA results showed that OVA induction increased the contents of eotaxin and RANTES in mouse NALF, while miR-181a-5p overexpression treatment reversed these trends (p < 0.01; Fig.…”
Section: Mir-181a-5p Overexpression Protected Against Treg/ Th17 Immu...mentioning
confidence: 82%
“…EOS is a kind of granulated innate immune cells, and eosinophilic inflammation is typically related to the aggravation of asthma [51]. RANTES and eotaxin are critical chemoattractants for EOS [32,33]. OVA induction increased the contents of eotaxin and RANTES in NALF, while miR-181a-5p overexpression decreased their contents.…”
Section: Discussionmentioning
confidence: 99%
“…A first generation corticosteroid, dexamethasone, is no longer preferred due to its side effects ( 452 ). The second generation corticosteroids, including beclomethasone dipropionate (aerosol) ( 453 - 460 ), budesonide (aqueous) ( 461 - 463 ), ciclesonide (aqueous or aerosol) ( 464 - 466 ), flunisolide (aqueous), fluticasone furoate (aqueous) ( 467 - 470 ), fluticasone propionate (aqueous) ( 471 - 474 ), triamcinolone acetonide (aqueous) ( 475 - 476 ) and mometasone furotate (aqueous) ( 466 , 477 - 482 ) have been used in nasal spray preparations until today.…”
Section: Treatment Of Allergic Rhinitismentioning
confidence: 99%
“…181 Existing evidence indicates an inhibitory effect of Levalbuterol on airway smooth muscle cell proliferation and cell growth, possibly by activating the cAMP/PKA pathway and inhibiting phosphoinositide 3-kinase (PI-3 kinase), NF-kB and retinoblastoma (Rb) protein expression. 182 Despite increasing the dose of inhaled corticosteroids, the addition of long-acting β-agonist salmeterol offers a better therapeutic response in asthmatic control. 212 Bronchodilators such as β-agonist and anticholinergic agents have been a good choice in patients with asthma and chronic obstructive pulmonary disease (COPD); however, the administration of β-agonist has been associated with side effects including the risk of cardiovascular complicacy, arrhythmias, hypoxemia, tachycardia, palpitations, and inflammatory response.…”
Section: Eosinophils In Modulating Epithelial Injurymentioning
confidence: 99%